Hypnotic drug use and intraoperative fluid balance associated with postoperative delirium following pancreatic surgery: A retrospective, observational, single-center study. - Zhi-Hua Huang; Jun Zhang; Xiao-Ying Xu; Ying Wang; Xiao-Jian Lu; Yan Luo (PLoS ONE)
Background Postoperative delirium is a common complication after various types of major surgery. The aim of this study was to identify risk factors associated with delirium following pancreatic surgery. Methods Data from the patients who had pancreatic surgery between July 2020 and March 2021 in Ruijin Hospital affiliated with Shanghai Jiao Tong University School of Medicine were retrospectively analysed. The postoperative risk factors related to delirium were analyzed by univariate and multivariate Logistic regression analysis. Results 59 of 385 patients (15.3%) developed postoperative delirium after pancreatic surgery. The ROC curve revealed the optimal cutoff of intraoperative fluid balance was 2863ml. Furthermore, the multivariate analysis demonstrated that age ≥  65 years old [Odds ratio (OR) 2.01; 95% Confidence interval (CI) 1.12-3.63; p =  0.019], hypnotic drug use (OR 4.17; 95% CI 1.50-11.10; p =  0.005), and intraoperative fluid balance (OR 2.57; 95% CI 1.37-4.84; p =  0.003) were the independent risk factors of postoperative delirium. Conclusion This study identified that intraoperative fluid balance and hypnotic drug use were independent risk factors associated with postoperative delirium development after pancreatic surgery.